Information, Motivation, and Self-Efficacy among Men Who Have Sex with Men and Transgender Women in the State of Maharashtra, India - Wilkerson, J. Michael (Health Educ Behav, 2018)
BACKGROUND: India’s National AIDS Control Programme calls for, among other things, targeted behavioral interventions that address determinants contributing to new infections among men who have sex with men (MSM) and hijras (transgender women). AIM: To determine if the information-motivation-behavioral skills (IMB) model was transferable to an Indian context. METHODS: We recruited 442 MSM and 7 hijras into an online cross-sectional study that asked questions about condom use knowledge, motivation, self-efficacy, and sexual behavior. Structural equation modeling was used to test the overall IMB structure. RESULTS: Overall fit of the model was good: χ(2)(201, N=447)=445.002, p<0.0001, RMSEA=0.052, 90%CI [.046, .059], CFI=.989, TLI=.987. Condom use and HIV risk knowledge did not significantly predict condom use self-efficacy or having condomless anal sex with more than one male partner in the past 3 months, and knowledge was not significantly correlated with attitudes toward barebacking. Despite this, the final structural model explained 14.4% of the variance in condom use self-efficacy and 20.0% of the variance in risky sexual behavior CONCLUSION: The public health response to India’s HIV epidemic is currently different than in the West due to differences in medication access and public health infrastructure. As Indian MSM and hijras learn more about the effectiveness of viral suppression and hopefully have greater access to PrEP, researchers should monitor for changing attitudes towards condoms and be prepared to collaborate with the public health infrastructure to develop interventions that reinforce positive attitudes towards condom use.